Religiosity and Organizational Citizenship Behavior: a Study on Student Employees in South Tangerang - Arifianto, Chandra; Mutawali; Subekti, Heny (International Journal of Science, Technology & Management, 2020)
This study explored the concept of Organizational Citizenship Behavior (OCB) in relation to student employees. The dimensions of religiosity is used as an independent variable in this study. This study expands the extant research by examining OCB of student employees, where very few studies exist. For this research 174 student employees completed an online survey, where we looked to identify correlations between OCB and three dimensions: participation, importance and meaning. Data collection in this study used a qustionnaire that developed a variable of religiosity totaling 9 items and variables totaling 15 items which isusing multiple linear regression. The statistically significant correlation between three of these dimensions and OCB will help campusidentify and encourage OCB in their student employees. The result of study shows that there is effect of the participation dimension (XL) and the meaning dimension (X3), but there is no efect of the meaning dimension (X3) on OCB.